2014
DOI: 10.1016/j.scienta.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of accessions of ‘Reine Claude Verte’ plum using Prunus SRR and phenotypic traits

Abstract: European plum (Prunus domestica L.) cv ‘Reine Claude Verte’ is highly appreciated for its excellent organoleptic qualities. Despite its increasing demand, this cultivar is in the process of being eradicated in many commercial orchards because of its generally erratic fruit setting. This situation led us to explore the behaviour of particular accessions with the aim of evaluating if some of them can crop more regularly. For this purpose, we initially evaluated the putative diversity of 24 European plum accessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Our work also indicated that a reduced number of SSRs is sufficient to efficiently discriminate plum varieties [20]. We observed very few high pair-wise similarities (i.e., >0.9), which is consistent with the lack of sports and/or Essentially Derived Varieties (EDV) originating from formal breeding [49]. A reduced number of nuclear SSRs offers obvious advantages for screening large populations however, we cannot exclude that a higher number of SSRs or the implementation of DNA sequence-based approaches [50], may be necessary to discriminate very similar varieties or to solve cases of putative homonymy.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our work also indicated that a reduced number of SSRs is sufficient to efficiently discriminate plum varieties [20]. We observed very few high pair-wise similarities (i.e., >0.9), which is consistent with the lack of sports and/or Essentially Derived Varieties (EDV) originating from formal breeding [49]. A reduced number of nuclear SSRs offers obvious advantages for screening large populations however, we cannot exclude that a higher number of SSRs or the implementation of DNA sequence-based approaches [50], may be necessary to discriminate very similar varieties or to solve cases of putative homonymy.…”
Section: Discussionsupporting
confidence: 75%
“…Our work indicates that morphological measurements of the fruits are very useful for the description of local varieties, also because their use does not require sophisticated technologies. In addition to the known advantages of molecular fingerprinting, the combination of molecular and morphological data for the classification of traditional plum varieties is probably necessary to separate closely related accessions and sports, or to select variants and clones [49].…”
Section: Discussionmentioning
confidence: 99%
“…The number of SSR primer pairs used in the study is higher or equal to other recent molecular studies on the European plum (Decroocq et al, 2004;Horvath et al, 2011;Xuan et al, 2011;Halapija Kazija et al, 2014), albeit lower than the 16 SSRs used by Gharbi et al (2014). However, Gharbi et al (2014) analyzed a group of genetically very similar 'Reine Claude Verte' plum accessions, hence the need for a higher number of SSR markers.…”
Section: Ssr Polymorphismmentioning
confidence: 89%
“…However, Gharbi et al (2014) analyzed a group of genetically very similar 'Reine Claude Verte' plum accessions, hence the need for a higher number of SSR markers. Nine primer pairs amplified 204 distinct alleles in this study, or on average 22.7 alleles per locus.…”
Section: Ssr Polymorphismmentioning
confidence: 99%
“…European plums are cultivated in colder climates [92], showing higher chilling requirements (579-1323 CH) than Japanese plums (118-685 CH) ( Tables 5 and 6). The chilling requirements of European plum ranged from 579-678 CH for 'Reine Claude d'Oullins' to 1116-1323 CH for 'Reine Claude Noir' [93]. There is no data available on heat requirements in this species.…”
Section: Peach (P Persica)mentioning
confidence: 96%